Small City Job Markets: The Labor Market Behavior of Firms and Workers - Fortin, Gérald (Relations industrielles / Industrial Relations, 1961)
The article reviews the book, "Small City Job Markets: The Labor Market Behavior of Firms and Workers," by Richard C. Wilcock and Irvin Sobel, Institute of Labor and Industrial Relations, University of Illinois, Urbana, 1958.